Vergilius Lyricus: The Influence of the Greek Lyric and Elegiac Poets on the Aeneid - Fratantuono, Lee (Myrtia, 2024)
Relatively little work has been done on the influence of the Greek lyric and elegiac poets on Virgil’s Aeneid. Close consideration of a number of passages from the surviving corpus of archaic and classical Greek lyric and elegiac poetry will demonstrate the pervasive influence of these works on the Augustan epicist.